Educational Background Reputation and Corporate Social Responsibility Disclosure: Evidence from the CEO Tenure Phenomenon in Indonesia - Refina Dwike Wahono; Adib Minanurohman; Raden Roro Widya Ningtyas Soeprajitno (JASF: Journal of Accounting and Strategic Finance, 2026)
Purpose: In Indonesia, the CEO's educational background is considered the appropriate indicator of how the policy is grounded in interests and reasoning. The purpose of this study was to examine the relationship between the CEO's educational background and corporate social responsibility practice. Method: We focus on testing the sample of the firm that was following the Global Reporting Initiative (GRI) indicator with 295 sample firm-year observations from Indonesia 2016–2019. The data collected from the CSRD from the sustainability report that the company discloses manually, hand-collected the educational background of the CEO, the financial report, and the annual report from the company accessed in the Indonesia Stock Exchange (IDX) and the OSIRIS database. Findings: This study found that a better educational background doesn't always result in better policy. In some cases, the CEO has a negative relationship with CSR. Specifically, the results of this study indicate that CEOs with a bachelor's degree (S1) on both reputation measures are not associated with CSRD. Implications: This study provides an important implication that the reputation of a CEO’s educational background does not necessarily translate into more effective corporate policies. The findings highlight the need for boards to focus on substantive governance practices and decision-making capabilities, rather than symbolic credentials, when formulating strategic policies. Novelty/Value: This study offers novelty by exploring the impact of CEO educational background and tenure on CSR disclosure, while highlighting that CEO educational reputation does not always enhance their commitment to CSR activities.